Cover Image, Volume 31, Issue 2. (18th January 2018) - Gogiashvili, Mikheil; Horsch, Salome; Marchan, Rosemarie; Gianmoena, Kathrin; Cadenas, Cristina; Tanner, Berno; Naumann, Sabrina; Ersova, Diana; Lippek, Frank; Rahnenführer, Jörg; Andersson, Jan T.; Hergenröder, Roland; et al.
Abstract : The cover image, by Mikheil Gogiashvili et al., is based on the Research Article Impact of intratumoral heterogeneity of breast cancer tissue on quantitative metabolomics using high‐resolution magic angle spinning 1H NMR spectroscopy, DOI:10.1002/nbm.3862 .